The Effectiveness of a Programme Based on Integrating Differentiated Instruction into Eclectic Approach to Enhance Preparatory Stage Pupils’ EFL Writing Skills - Elghotmy, Heba Elsayed Abdelsalam (جامعة المنوفية - كلية التربية, 2022)
هدفت الدراسة الحالية إلى التحقق من فعالية برنامج يعتمد على دمج التدريس المتمايز في المدخل التوليفي لتعزيز بعض مهارات الكتابة (الوحدة، التماسك، القواعد، التنظيم، وآليات الكتابة) لتلاميذ المرحلة الإعدادية. استند جمع البيانات إلى نهج الأساليب المختلطة المتسلسلة، وبالتالي اعتمد البحث الحالي تصميم المجموعة التجريبية الواحدة في المرحلة الأولى من الدراسة، تم تطبيق مقياس الذكاءات المتعددة على العينة بأكملها لتقسيمها وفقا لذكائهم المهيمن حيث تم تقسيم الطلاب إلى ثلاثة مجموعات تجريبية: لفظية / لغوية، وبصرية / مكانية، ومنطقية / رياضية وقامت الباحثة بتطبيق قائمة مهارات الكتابة باللغة الإنجليزية كلغة أجنبية، واختبار الكتابة باللغة الإنجليزية كلغة أجنبية، ومقياس التقدير لاستخدامه في تقييم كتابات التلاميذ، استخدمت الباحثة أيضا برنامج يعتمد على دمج التدريس المتمايز في المدخل التوليفي لتسعين تلميذ وتلميذة في الصف الثاني الإعدادي بمحافظة المنوفية. وفي المرحلة الثانية، أجرت الباحثة مقابلات شبه منظمة مع خمسة عشر من معلمي المرحلة الإعدادية لاستنباط تصورات المعلمين حول دمج التدريس المتمايز في المدخل الانتقائي. تم تحليل البيانات كميا ونوعيا حيث كشفت النتائج أن البرنامج المقترح القائم على دمج التدريس المتمايز في المدخل التوليفي فعال في تعزيز مهارات الكتابة لدى تلاميذ المرحلة الإعدادية.
The current study aimed to investigate the effectiveness of a programme based on integrating differentiated instruction into the eclectic approach in enhancing some EFL writing skills (unity, coherence, grammar, organization, and mechanics of writing) of preparatory stage pupils. Data collection was based on a sequential mixed methods design; thus, the present research adopted a one group pre-posttest quasi experimental design in the first phase of the study. Multiple intelligences inventory was administered to the whole sample to divide them according to their strongest dominated intelligence. The pupils were divided into three experimental groups: verbal / linguistic, visual / spatial, and logical / mathematical. The researcher in the first phase of the study administered an EFL writing skills checklist, an EFL pre-post writing skills test, a scoring rubric to be used for grading pupils‟ writings, and a program based on integrating differentiated instruction into the eclectic approach to ninety students enrolled in the second year, preparatory stage, Menoufia governorate. In phase two, the researcher conducted semi-structured in depth interviews with 15 preparatory stage teachers to elicit their perceptions of integrating differentiated instruction into the eclectic approach. Data were analysed quantitatively and qualitatively. Findings revealed that the proposed program based on integrating differentiated instruction into the eclectic approach was effective in enhancing EFL preparatory stage pupils‟ writing skills.
Keywords: طلبة المرحلة الإعدادية -- اللغة الإنجليزية -- المهارات اللغوية -- طرق التدريس -- التدريس المتمايز